CONSUMER LAW PROTECTION AGAINST SOY CARTEL IN THE PERSPECTIVE OF UNFAIR COMPETITION LAW - Angriani, Parida (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
In general, competition is fair, if done honestly, but the competition is not always conducted honestly. It can be seen from the number of cases that decided by the Commission Business Competition Supervision (KPPU) on fraudulent acts committed by company. One of fraudulent acts is Cartel. Cartels are agreements made by businesses to other businesses in similar production to influence prices and production process. The cartel actions usually choose products that have strategic value, such as soy. Soybean is the basic ingredient that can be processed into a variety of food and beverage. But lately soybean prices are very high and causing consumer suffers losses. Skyrocketing soybean prices in the market, causing losses to consumers that can held responsibility under the law to the company, administrative and criminal sanctions. Today, soybean production are indicated the soy cartel. To avoid such allegations, in the production of soybean company must be obey on Law Number 5 Year 1999 on Prohibited Monopoly Practices and Unfair Competition. The law prohibited cartel action by company that set in Article 11. But cartel arrangement was deemed less clear and incomplete, because it does not provide clear and unequivocal definition of cartel and cartel types. So to avoid the vagueness of norms, government in formulating the law must be carefully and able to provide legal protection to consumers so that can prevent the arbitrary actions by company. Keywords: Cartel, Soybean, and Unfair Business Competition.